Deposition of non-spherical particles in bifurcating airways. (28th November 2013) - Bunchatheeravate, Poom; Curtis, Jennifer S.
Abstract: Particle morphology plays an important role in pulmonary drug delivery. Not only does particle shape affect how particles flow and deposit, the shape also influences the drug release rate from the particles. In this work, a semi-theoretical relationship is developed to describe deposition efficiency as a function of fluid and particle properties, incorporating the effect of particle shape. For the 10 different particle types studied (with aerodynamic diameters between 1 and 10 µm), three key deposition mechanisms are identified. All particles deposit through inertial impaction, and additionally deposit via sedimentation or diffusion, depending on the particle specific momentum.